THE PROPOSED MODEL OF THE INTEGRATION OF THE PRINCIPLE OF MAQASID AL- SHARIAH IN MANAGERIAL DECISION MAKING PROCESS IN SHARIAH-COMPLIANT SECURITIES - Nurul Nadirah Binti Abu Hasan; Khairunnezam Bin Mohd Noor; Ahmed Abdul Malik; Zulkifli Abdul Ghani (Journal of Islamic, Social, Economics and Development, 2018)
The main focus of this paper is to propose an idea of the integration of the principle of Maqasid Al-Shariah in managerial decision making process among organization in Malaysia. This paper will focus on the importance of integrating Maqasid Al-Shariah in managerial decision making process of consumer product in Shariah-compliant securities. Maqasid Al- Shariah which is derived from the Quran and Hadith will be promoted as the greatest method to assure the best practice in developing effective managerial decision making process. It is hoped that based on the paper, organization in Malaysia are more open in accepting and practicing the principles of Maqasid Al-Shariah in their managerial decision.